Driving cross selling in South African business to business firms - Makhene, Mpho (My University, 2015)
Cross-selling remains the easier and most cost effective option for companies to grow revenues and achieve profitability as compared to growing revenue by acquisition of new customers. Many firms are seeking to grow their revenue and achieve high levels of customer loyalty. These firms and industries across the world are turning to cross selling as the solution. Many factors, such as merger and takeovers, result in firms having multiple product lines and silos with sales people focused according to these product divisions. What becomes more difficult is identifying which factors will lead to more integrated teams that are motivated to engage in cross selling. This study seeks to address some of the challenges that result in lower motivations levels of sales people to engage in cross selling. Financial incentives, product knowledge and recognition are studies to determine their influence on motivation to cross sell products from other divisions in a firm. A review of literature was conducted to study the influence of financial incentive, product knowledge and personal recognition on work motivation. These three constructs were then extended into a quantitative study of how they influence sales people’s motivation to engage in cross selling. The findings uncovered that salespeople consider product knowledge as a key inhibitor for them to engage in cross selling. The results also revealed a close contest with financial incentives and personal recognition also having positive influence on their motivation to engage in cross selling. Consistent with existing literature from social studies, it cannot be overemphasised that product knowledge empowers sales people and gives them the confidence to cross sell in an industrial sales environment.
Thesis (M.M. (Strategic Marketing))--University of the Witwatersrand, Faculty of Commerce, Law and Management, Graduate School of Business Administration, 2015.
Keywords: Sales; Cross selling; Motivation; Financial incentives; Recognition; Product knowledge